Sterling in decline : - Cairncross, Alec (Palgrave Macmillan, 2003)
This is a new edition of Sterling in Decline with a new introduction by Barry Eichengreen. The book traces the decline of sterling from the world's pre-eminent currency alongside the dollar's rise to prominence. There are parallels to be drawn with the euro's emergence as a full-fledged competitor to the dollar for international currency status. The new introduction will bring sterling's story up to date and draw out the implications for the dollar and the euro.